PENGARUH JENIS UMPAN TERHADAP HASIL TANGKAPAN IKAN PANCING LAYANG-LAYANG DI SELAT BANGKA KABUPATEN MINAHASA UTARA - Takapaha, Stevenly A; Kumajas, Henry J; Katiandagho, Elof M (Sam Ratulangi University, 2010)
Hound needlefish (Cendro or Sako) (Tylosurus sp.) including the types of fish are hard to catch because the surface movements and jumps very agile, is an effective fishing gear to catch this fish is to use a kite fishing. This study aimed to see whether there is the influence of several kinds of bait such as: blue sprat (Spratelloides robustus), sardines (Amblygaster sirm), fish cutlet mackerel scad (Decapterus macarellus), and anchovy (Stolephorus indicus) of the catch. The method used is descriptive. Â Data was collected by use four units of fishing kites gear with four types of bait treatment. Â Based on the analysis we found that the type of bait blue sprat better than mackerel scad and anchovy bait but not significantly different from the bait sardines, which are types of fish caught is Strongylura indicus (4%), Tylosurus Crocodiles (90%) and Tylosurus acus melanotus (6%).